Genetics of dementia: Update and guidelines for the clinician - Cohn-Hokke, Petra E.; Elting, Mariet W.; Pijnenburg, Yolande A.L.; van Swieten, John C. (American journal of medical genetics. Part B, Neuropsychiatric genetics, 2012)
With increased frequency, clinical geneticists are asked for genetic advice on the heredity of dementia in families. Alzheimer's disease is in most cases a complex disease, but may be autosomal dominant inherited. Mutations in the PSEN1 gene are the most common genetic cause of early onset Alzheimer's disease, whereas APP and PSEN2 gene mutations are less frequent. Familial frontotemporal dementia may be associated with a mutation in the MAPT or GRN gene, or with a repeat expansion in the C9orf72 gene. All these genes show autosomal dominant inheritance with a high penetrance. Although Alzheimer's disease and frontotemporal dementia are clinically distinguishable entities, phenotypical overlap may occur. Rarely, dementia is caused by mutations in other autosomal dominant genes or by genetic defects with autosomal recessive, X‐linked dominant or mitochondrial inheritance. The inherited forms of frontotemporal dementia and Alzheimer's disease show a large phenotypic variability also within families, resulting in many remaining uncertainties for mutation carriers. Therefore, genetic counseling before performing genetic testing is essential in both symptomatic individuals and healthy at risk relatives. This review provides an overview of the genetic causes of dementia and discusses all aspects relevant for genetic counseling and testing. Furthermore, based on current knowledge, we provide algorithms for genetic testing in patients with early onset Alzheimer's disease or frontotemporal dementia. © 2012 Wiley Periodicals, Inc.